Acceptance of Islamic finance products: a study on muslim consumers attitude in a non Muslim country - Yusoff, Mohd. Effandi (Penerbit UTM, 2008)
In accordance with the teachings of Islam which prohibit the utilisation of Riba (interest), this has led to the development of a banking approach which are based on the laws of shariah. Although these methods are not totally new or revolutionary as it has been written and practiced during the renaissance of the Islamic civilisation, it has yet to establish itself and tested in the modern world as compared to the conventional banking. Many Muslims worldwide still engage in non-interest-free in financing their purchases especially those who are staying in non-muslim countries. There are many reasons why Muslims still engage in non-interest-free products. one of the reasons is the availibility of Muslim financial product or non-interest bearing financial instruments offers by the banks. it is quite difficulut to find such instruments as most of them are not easy to get. To some extent, there are only a few financial instituitions that offer such products products among Muslims outside the Islamic world and will explain whether there is demand for such product from Muslims staying in non Muslim countries. The study reveals that Muslims living in non Muslim countries are very much willing to change their practices from the conventional system into the new system – the Islamic financial system.